Spatial variability of total nitrogen, and available phosphorus of large rice field in Sawah Sempadan Malaysia - Mohamed Ganawa, Eltaib Saeed; Mohd Soom, Mohd Amin; Musa, Mohd Hanafi; Mohamed Shariff, Abdul Rashid (Science Society of Thailand under Royal Patronage, 2003)
Accurate information on the spatial variability of soil chemical properties is very important in developing site-specific management for large rice field. Therefore, sampling procedure for soil nutrients status validated for developing variable rate of application of nutrients for rice is essential. Variability of total nitrogen(N), and available phosphorus(P) was examined on 2300 ha rice field. The soil samples (n=240) were taken from 120 points; two points in each plot were taken at two depths: top-soil (0-20 cm) and sub-soil (20-30 cm). Collection of the soil samples has been done in order to cover all types of the soil series dominant in the study area. Differential global positioning system (DGPS) was used to locate the sample position, and variability of soil chemical properties was analysed by geostatistical techniques. Total N, and available P varied greatly for both depths as indicated by variogram analysis. The range of total N varied between 0.434 and 0.475 km for top- and sub-soil depth, respectively, and available P between 0.597 and 0.610 km for top- and sub-soil depth, respectively. The kriging maps showed the spatial variation for soil chemical properties measured. The results suggest that soil chemical properties measured may be useful in the field management zones that could maximize application benefits. © 2003 Science Society of Thailand under Royal Patronage. All rights reserved.